Fatigue and recovery measured with dynamic properties versus isometric force: effects of exercise intensity - Krüger, R. L.; Aboodarda, S. J.; Jaimes, L. M.; MacIntosh, B. R.; Samozino, P.; Millet, G. Y. (The Journal of Experimental Biology, 2019)
Although fatigue can be defined as an exercise-related decrease in maximal power or isometric force, most studies have assessed only isometric force. The main purpose of this experiment was to compare dynamic measures of fatigue [maximal torque (Tmax), maximal velocity (Vmax) and maximal power (Pmax)] with measures associated with maximal isometric force [isometric maximal voluntary contraction (IMVC) and maximal rate of force development (MRFD)] 10 s after different fatiguing exercises and during the recovery period (1-8 min after). Ten young men completed six experimental sessions (3 fatiguing exercises×2 types of fatigue measurements). The fatiguing exercises were: 30 s all-out intensity (AI), 10 min at severe intensity (SI) and 90 min at moderate intensity (MI). Relative Pmax decreased more than IMVC after AI exercise (P=0.005) while the opposite was found after SI (P=0.005) and MI tasks (P<0.001). There was no difference between the decrease in IMVC and Tmax after the AI exercise, but IMVC decreased more than Tmax immediately following and during the recovery from the SI (P=0.042) and MI exercises (P<0.001). Depression of MRFD was greater than Vmax after all fatiguing exercises and during recovery (all P<0.05). Despite the general definition of fatigue, isometric assessment of fatigue is not interchangeable with dynamic assessment following dynamic exercises with large muscle mass of different intensities, i.e. the results from isometric function cannot be used to estimate dynamic function and vice versa. This implies different physiological mechanisms for the various measures of fatigue.